Soil microbes promote complementarity effects among co-existing trees through soil nitrogen partitioning - Luo, Shan; Schmid, Bernhard; De Deyn, Gerlinde B.; Yu, Shixiao (Functional ecology, 2018)
Plant resource partitioning is a mechanism promoting species coexistence and ecosystem functioning. Yet, we still have limited understanding of how soil microbes, especially plant symbiotic microbes, influence resource partitioning. We hypothesized that soil‐borne microbes, in particular mycorrhizal fungi, facilitate differential performance of tree species depending on different nitrogen sources and that this leads to a positive plant diversity–community productivity relationship. We conducted two complementing glasshouse experiments. In a “monoculture experiment,” we supplied nitrogen as ammonium, nitrate or glycine and tested the growth response of three tree species associated with different root symbionts: one associated with ectomycorrhizal fungi, one associated with arbuscular mycorrhizal fungi, and the third associated with both arbuscular mycorrhizal fungi and N‐fixing bacteria. In an “intermixed experiment,” we grew the tree species at three richness levels (one, two or three species) in soil supplied with a mix of the three nitrogen forms or no added nitrogen, and with or without soil microbes. The monoculture experiment showed that in the presence of soil microbes, the ectomycorrhizal plant species grew best when supplied with glycine and the two arbuscular mycorrhizal plant species grew best with either nitrate or ammonium addition. When the different forms of nitrogen were mixed in the intermixed experiment, plant mixtures produced more biomass than plant monocultures in the presence of soil microbes, with positive complementarity effects indicating microbe‐mediated plant resource partitioning. Our results suggest that co‐existing tree species can partition soil nitrogen when grown with their particular mycorrhizal symbionts or other soil microbes, resulting in positive biodiversity effects in complex resource environments. A plain language summary is available for this article. Plain Language Summary